Fate of Listeria monocytogenes on ready-to-eat meat products, treated with antimicrobials, and under conditions simulating passage through the human stomach and small intestine - Barmpalia-Davis, Ioanna Maria, author; Sofos, John, advisor (Colorado State University. Libraries, 2008)
To cause infection, the foodborne pathogen Listeria monocytogenes must overcome stresses associated with food processing, storage, and preparation, as well as various defense elements of the human body. In this work, we examined factors that may affect growth and survival properties of this pathogen on foods and during passage through a simulated stomach and small intestine.

One study was conducted to evaluate the antilisterial effectiveness of the naturally occurring protein lactoferrin and its activated form (ALF), as a formulation ingredient or as surface treatment, respectively, in comparison or in combination with organic acids and salts on various ready-to-eat (RTE) meat and poultry products. Overall, findings suggested that lactoferrin used in product formulations and ALF applied as a surface treatment were not as effective as established antimicrobials. Application of ALF or lactoferrin enhanced the antilisterial activity of other antimicrobial ingredients (potassium lactate and sodium diacetate or lactoferrin) or dipping treatments (acetic acid), respectively, suggesting that appropriate combinations of these natural antimicrobials with chemical compounds may be effective in controlling L. monocytogenes on RTE products.

Three studies investigated survival patterns of L. monocytogenes during passage through the upper gastrointestinal tract in a sequential manner by utilizing a dynamic model of the stomach and small intestine. The studies tested pathogen- (e.g., strain variation, growth phase) and food- (e.g., pH, fat content) related factors that could influence the resistance of the pathogen to stresses prevailing in the gastrointestinal tract. Findings indicated that gastric survival of this pathogen was influenced by factors, including strain variation, the type (i.e., bologna vs. salami) and the fat level of the product. However, due to the gradual acidification of the gastric contents (pH 2.0 within 88 min) and the fact that gastric emptying started while the pH of the stomach was still high, populations being transferred in the intestinal compartment (pH ~6.5) were affected by the initial (0 min) contamination levels. Thus, pathogen counts in the simulated intestine depended on the growth potential of the pathogen, as affected by the strain, characteristics of the food matrix, or the length of the storage period, particularly since intestinal stresses caused slight reductions in populations.
Keywords: antimicrobials; gastrointestinal; Listeria monocytogenes; meat products; ready-to-eat; agronomy; microbiology; food science